(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2020)
CoCrMo alloys are used as biomaterial due to their good corrosion and wear resistance, with reasonable biocompatibility. The present study aims to investigate the effect of (1, 3 and 5) wt% ?-Al2O3 nanoparticle additions on some properties of pre-alloyed CoCrMo when fabricated by powder metallurgy route. The density, porosity, microhardness and microstructure of the fabricated samples were examined. The results revealed that the addition of ?-Al2O3 nanoparticle has a distinguished effect on the density of sintered CoCrMo alloy samples, where continues increase in the porosity was happened and reached to its maximum value at the higher addition amount. While the density showed an inverse trend to that of the porosity with the increasing of the nanoparticle addition. The microhardness was decreased as the amount of the nanoparticle addition to CoCrMo alloy was increased. The microstructure observation by SEM and SEM-Mapping is revealed the partial isolation of CoCrMo particles by the nanoparticle additions and it was associated with the formation of passive Cr2O3 oxide. In turn the XRD analysis depicted the co-existence of ?-Co and ?-Co phases besides, the Cr2O3 oxide. Although the increased porosity with the nanoparticle addition but, this will perhaps, increase the tissue ingrowth when the fabricated nanocomposites were utilized as biomaterial